MAKNA PARUNTUK KANA PADA PROSESI ASSONGKBALA DI GALESONG TAKALAR: Meaning of Paruntuk Kana in Assongkbala Procession in Galesong Takalar - Machdi, Andini; Daeng, Kembong; Hajrah (Journal of Applied Linguistics and Literature, 2024)
This research aims to reveal the meanings that exist in the Assongkabala procession procession in Galesong, Takalar Regency. The results showed that the analysis of the meaning of paruntuk kana in the Assongkabala procession in Galesong, Takalar Regency presented the symbolic meaning of: (1) Attunu incense (2) Esaki tamparang leklenga nampa antakle anyombalang (3) Apalele umbu (4) Songkolok asepunu lekleng sagang songkolok asepunu kebo (5)nataba karro (6) Kappara gallang (7) leko ri talang bulaeng (8) attongrang (9) Apparappo ri tamparanga (10) Tena na sambarang allo assongkabala allo jumapi (11) Babbaraki buttaya. The meaning contains turiolo advice that is useful for people who listen. Traditional rituals such as the Assongkabala procession are very important to maintain their existence because apart from being a legacy of ancestors, they can also maintain social stability in society and religion because they foster a sense of togetherness and solidarity in society and family.